The effects of antioxidant combination on indomethacin-induced gastric mucosal injury in rats - Turkyilmaz, Ismet Burcu; Coskun, Zeynep Mine; Bolkent, Sema; Yanardag, Refiye (Cellular and Molecular Biology, 2019)
The aim of this study is an investigation the protective effects of vitamin C (Vit C), vitamin E (Vit E), Î²-carotene, sodium selenate combination in indomethacin-induced gastric mucosal damage in rats. Rats were divided into 6 groups. Group I: Intact animals (control). Group II: Control animals receiving Vit C (100 mg/kg/day), Vit E (100 mg/kg/day), Î²-carotene (15 mg/kg/day) and sodium selenate (0.2 mg/kg/day) for 3 days. Group III: Animals receiving 25 mg/kg indomethacin. Group IV: Animals receiving Vit C, Vit E, Î²-carotene and sodium selenate (in same doses) for 3 days 2 h before the administration of indomethacin. Group V: Animals receiving ranitidine (150 mg/kg) for 3 days. Group VI: Animals receiving ranitidine for 3 days 2 h before to the administration of indomethacin (in same dose and time). The administration of indomethacin caused a decrease in the levels of glutathione, mucus, hexosamine and in the activities of glutathione-S-transferase, sodium-potassium ATPase, thromboplastic activity and an increase in the aspartate and alanine amino transferase, alkaline phosphatase, catalase, lactate dehydrogenase, myeloperoxidase activities and sialic acid, lipid peroxidation and protein carbonyl levels. Stomach caspase-8 immun+ cell numbers showed a slight increase while caspase-9 immun+ cell numbers reduced in indomethacin given group compared to control animals. Our results findings suggest that the combination of Vit C, Vit E, Î²-carotene, sodium selenate and ranitidine has a protective effect on indomethacin-induced gastric mucosal injury of rats.